If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 2x + -1 = 0 Reorder the terms: -1 + -1x + 2x = 0 Combine like terms: -1x + 2x = 1x -1 + 1x = 0 Solving -1 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 1x = 0 + 1 1x = 0 + 1 Combine like terms: 0 + 1 = 1 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| 650+88m=650m | | 247*11= | | 2x-14=x+40 | | 0=-12x^2+156x | | 6[1-(5x-2)]=8(3-3x) | | 4q-34=2q | | 3x+15=1x+21 | | 40c^2/8c | | z(z+1)=11+3i | | 7+2z=13 | | 4q-34=29 | | -12x^2+12=156x | | 6p+27=9p | | ax^2+12x+9=0 | | −5=f/5 | | z(z-1)(z+3)=11+3i | | 3ax^2+2ax-1=0 | | (4x-6)/5=90 | | 8-(4n-8)=-8 | | 2(x-1)=3x-7 | | 25-2x=15 | | 1.8x-8=22 | | 2x-(-4)=96+(-10) | | 3x+4y=9.4 | | 4z/6-6=5 | | d/12-6=1 | | -8x+2=74 | | 6=-3+v | | -18a/6 | | 3x+4x=9.4 | | f(x)=3x^4-13x^2+14 | | 1.8q-5.4-1.7q=-0.9q-5.1 |